Factors contribute towards safety awareness among students in teaching laboratories at Northern Peninsular of Malaysia public university - Abdul Muhaimin, Mohaidin (2020)
The purpose of this study is to determine the relationship of safety commitment, management commitment and safety rules and procedure towards safety awareness among student in teaching laboratories at public university. The independent variables are safety commitment, management commitment, safety rules and procedures while the dependent variable is safety awareness. A total of 250 participated in this study by answering survey questionnaire. Data was collected through 55 items questionnaires on a five-point Likert scales and another 7 items were demographic questions. Data was analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (correlation and multiple regressions). The findings from this study showed that safety commitment, management commitment, safety rules and procedure have significant relationship with safety awareness. Based on multiple regression result, among independent variables, safety commitment shows the highest level of regression variance accounted for safety awareness variables which is 39% of the factors studied. The most influential factor is safety commitment, followed by management commitment and safety rules and procedure. The recommendation is students should be more responsible and commit to comply the regulation of Occupational Safety and Health (OSH) in the area of teaching laboratories in the public university. Furthermore, faculty management should encourage student participation in programme of OSH (Occupational Safety and Health) organized by the faculty of management is important.